Design and validation of an observation instrument for technical and tactical actions in indoor volleyball - Jose M Palao; Policarpo Manzanares; Enrique Ortega (Asociación Española de Ciencias del Deporte, 2015)
The purpose of this paper was to design and validate an observation instrument to analyse technical and tactical actions in indoor volleyball. The instrument collects information regarding: a) information about the match (context), b) information about game situations, c) information about technical situations (serve, reception, set, attack, block, and court defence) in relation to player that intervenes, role, manner of execution, execution zone, and efficacy, and d) information about the result of the play (win-lose, and way point is obtained). Instrument design and validation was done in seven stages: a) review of literature and consultation of experts; b) pilot observation and data analysis; c) expert review of instrument (qualitative and quantitative evaluation); d) observer training test; e) expert review of instrument (content validity); f) measurement of the predictive ability of the instrument (winning-losing); and g) measurement of the differences between playing situations (practice and competition). The results show that the instrument allows for obtaining objective and valid information about the players and team in offensive and in defensive actions, as well as indirectly from physical actions.